1986
DOI: 10.3109/00365528609034638
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Disease: Acute and Maintenance Treatments with Cimetidine

Abstract: The comparative efficacy of a 12-week acute treatment with 800 and 1600 mg cimetidine daily and the effectiveness of a 400-mg single-dose maintenance treatment versus placebo lasting 6 months were studied in a double-blind fashion in 30 and 24 patients, respectively, with gastroesophageal reflux (GER) disease. Cimetidine in a dose of 800 or 1600 mg daily resulted in a significant symptomatic improvement and a decrease in the extent of endoscopic esophagitis. An improvement in the gastroesophageal sphincter fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Another study analysed a six months maintenance treatment with cimetidine or placebo in 24 patients. 17 Sustained symptomatic relief was similar in both groups when only patients were considered who completed the observation period. Because four of 10 patients in the placebo group dropped out because of worsening symptoms, their data are therefore in accordance with our results.…”
Section: Discussionmentioning
confidence: 78%
“…Another study analysed a six months maintenance treatment with cimetidine or placebo in 24 patients. 17 Sustained symptomatic relief was similar in both groups when only patients were considered who completed the observation period. Because four of 10 patients in the placebo group dropped out because of worsening symptoms, their data are therefore in accordance with our results.…”
Section: Discussionmentioning
confidence: 78%
“…Maintenance with H2 receptor antagonists, at doses lower than those given for acute curative treatment (ranitidine 150 mg once a day, famotidine 20-40 mg once a day, cimetidine 400-800 mg twice a day), has not been shown to be efficacious in preventing symptom or endoscopic relapse compared with placebo. [12][13][14][15][16][17][18][19][20][21] Similarly, one study with omeprazole showed that for patients to remain in remission a dose of 40 mg once a day had to be giventhat is, the dose given in the acute healing phase.22 However, prolonged treatment with omeprazole has not been adequately assessed either for efficacy or for safety.323 To date, one paper has suggested that prophylaxis of relapse may be achieved with the full therapeutic dose of ranitidine. 28 Our study provides the first evidence for the efficacy of a prokinetic drug to maintain remission in patients with oesophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest recommended dose for each drug is as follows: cimetidine, 400 mg; ranitidine, 150 mg; famotidine, 20 mg; and nizatidine, 150 mg, twice daily for 6–12 weeks. These regimens produced healing in 17–70% and improvement of symptoms in 32–82% of patients (94–106). Rates of improvement of 45–75% have been reported with high doses of H 2 ‐receptor antagonists (cimetidine, 800 mg; ranitidine, 300 mg; famotidine, 40 mg; nizatidine, 300 mg; all twice daily) (91, 103, 123).…”
Section: Therapy Of Gerdmentioning
confidence: 99%